(untitled) (Research, Society and Development, 2022)
This study aimed to describe the clinical-epidemiological profile of cases of congenital heart disease treated at a referral hospital in the state of Pará - Brazil. Ecological, descriptive, retrospective, population-based study, where data from the register of patients treated between January 2012 and December 2016 were used, and the 2010 Census database was used to decode the information from the municipalities of origin. and the IBGE’s millionth system. All patients had a diagnosis confirmed at least by echocardiogram. The variables were: gender, age, type of heart disease, treatment performed and waiting time. Of the 905 cases observed, 52% were over 1 year of age at diagnosis, 75.1% had acyanotic heart disease, with ventricular septal defect being the most frequent (21%). Among cyanotic heart diseases, Tetralogy of Fallot was the most frequent (12%). There was no gender predominance. At the time of evaluation, 55.7% of the patients were awaiting treatment, 33.8% had undergone surgery, 5.3% had undergone surgery and underwent hemodynamic treatment, and 5.2% had undergone treatment exclusively, hemodynamic. The lethality during the study period was 9.61%, of which 83.9% had undergone surgical treatment. There are difficulties in accessing diagnosis and treatment, especially in municipalities further away from the state capital.